On the typology of motion events in Aymara (Atti del Sodalizio Glottologico Milanese, 2021)
This paper investigates the lexicalization pattern of motion events in Aymara, an Andean language spoken in Bolivia, Peru, and Chile. After providing a description of the morphosyntax of translational motion events, this study aims at a preliminary typological classification of Aymara within the framework of Talmy’s typology (Talmy 2000). With this purpose, three diagnostic tests have been used to determine the basic framing-typology of motion events. These tests consider i) the size of manner-of-motion lexicon and, more broadly, the degree of manner salience, ii) the complex-path constructions and the use of ‘plus-ground’ clauses, iii) the expression of boundary-crossing. The results of this analysis are in line with predictions of expected values according to Talmian typology, and suggest that Aymara is a predominantly satellite-framed language.